Transformational vs Transactional Leadership and Organizational Ambidexterity for Innovation : A Systematic Literature Review: Kepemimpinan Transformasional vs Transaksional dan Ambidexteritas Organisasi untuk Inovasi : Tinjauan Literatur Sistematis - Gerson Manurung; Bambang Karsono; Tri Widyastuti (Jurnal Bisnis dan Ekonomi, 2026)
Objective : This study aims to analyze and compare the influence of Transformational Leadership (TL) and Transactional Leadership (TR) on organizational innovation and ambidexterity (exploration and exploitation) in the digital era.   Methods : Using a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework, this research reviewed 42 scholarly articles published between 2015 and 2025 from databases including Scopus, Web of Science, SAGE, and ScienceDirect. Results : The results indicate that transformational leadership supports explorative innovation, while transactional leadership strengthens exploitative innovation. Together, they create organizational ambidexterity that enables sustainable innovation and adaptability in the digital era.